Leadership Lessons from Navigating COVID-19 - Christopher Hirschler PhD (Academic Chairpersons Conference Proceedings, 2022)
Chairs played a key role in navigating important university decisions and communication during COVID-19, a hypersensitive time when mortality salience was elevated. We will explore leadership styles, view brief excerpts of videos that were created to celebrate degree completion and improve retention. Participants will distill “lessons learned” from a challenging year.
Keywords: COVID-19; academic leadership; servant leadership; situational leadership